2008
DOI: 10.1186/1471-2407-8-306
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenesis therapy based on the bone marrow-derived stromal cells genetically engineered to express sFlt-1 in mouse tumor model

Abstract: BackgroundBone marrow-derived stromal cells (BMSCs) are important for development, tissue cell replenishment, and wound healing in physiological and pathological conditions. BMSCs were found to preferably reach sites undergoing the process of cell proliferation, such as wound and tumor, suggesting that BMSCs may be used as a vehicle for gene therapy of tumor.MethodsMouse BMSCs were loaded with recombinant adenoviruses which express soluble Vascular Endothelial Growth Factor Receptor-1 (sFlt-1). The anti-angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…These findings suggest that therapies using allogeneic MSCs may also be immune suppressive, and clearly this is a relevant issue that must be addressed in the context of tumor therapy. Lewis lung carcinoma [36] Inhibit growth of lung metastasis and prolong survival VEGFR-1 Lewis lung carcinoma [38] Decrease lung metastases and prolong lifespan HSV-Tk Leptomeningeal glioma [37] Reduce tumor size and prolong survival rMSC HSV-Tk Glioma [39] Tumor growth suppression and survival prolongation Glioblastoma [40,41] iNOS Fibrosarcoma [42] Inhibit tumor growth hBM-MSC, human bone marrow-derived mesenchymal stem cell; hAT-MSC, human adipose tissue-derived mesenchymal stem cell; hUCB-MSC, human umbilical cord blood-derived mesenchymal stem cell; mMSC, mouse bone marrow-derived mesenchymal stem cell; rMSC, rat bone marrow-derived mesenchymal stem cell.…”
Section: Mscs Are Immune Privilegedmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that therapies using allogeneic MSCs may also be immune suppressive, and clearly this is a relevant issue that must be addressed in the context of tumor therapy. Lewis lung carcinoma [36] Inhibit growth of lung metastasis and prolong survival VEGFR-1 Lewis lung carcinoma [38] Decrease lung metastases and prolong lifespan HSV-Tk Leptomeningeal glioma [37] Reduce tumor size and prolong survival rMSC HSV-Tk Glioma [39] Tumor growth suppression and survival prolongation Glioblastoma [40,41] iNOS Fibrosarcoma [42] Inhibit tumor growth hBM-MSC, human bone marrow-derived mesenchymal stem cell; hAT-MSC, human adipose tissue-derived mesenchymal stem cell; hUCB-MSC, human umbilical cord blood-derived mesenchymal stem cell; mMSC, mouse bone marrow-derived mesenchymal stem cell; rMSC, rat bone marrow-derived mesenchymal stem cell.…”
Section: Mscs Are Immune Privilegedmentioning
confidence: 99%
“…Subsequently, MSCs from different sources, including human bone marrow-derived MSCs [28][29][30][31], human adipose tissue-derived MSCs (hAT-MSCs) [32,33], human umbilical cord blood-derived mesenchymal stem cells [34], mouse bone marrow-derived MSCs (mMSCs) [35][36][37][38], and rat MSCs [39][40][41][42], have been evaluated as vehicles for tumor therapy. The expression of diverse therapeutic genes, including IFN-b [27,28,30], TRAIL [29,32,34], PEDF [33], IL-12 [35], CX3CL1 [36], VEGFR-1 [38], iNOS [42], and HSV-Tk [37,[39][40][41], has been engineered into MSCs to allow a targeted release of these agents in models of melanoma [27,28], breast cancer [29,35], Lewis lung carcinoma [36], gliomas [30,34,37,39], glioblastoma [40,41], cervical cancer [32], prostate cancer [33], and fibrosarcoma [42]. In each of these tumor models, treatment showed efficacy in the inhibition of local tumor g...…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying the vascular growth likely involves the regulation of soluble FLT1 (sFLT1) expression in the corneal epithelium. sFLT1 has been shown to be a general regulator of corneal avascularity (Ambati et al 2006), in addition to its role as a suppressor of angiogenesis in tumors (Zhang et al 2005;Liu et al 2007;Hu et al 2008;Ramachandra et al 2009). Our finding that SRF overexpression leads to downregulation of such a critical molecule for the maintenance of avascularity may be of extreme clinical significance and could explain why cancers associated with increases in SRF are highly tumorigenic and have significant rates of metastases (Park et al 2007;Genin et al 2008;Choi et al 2009;Medjkane et al 2009).…”
Section: /Srfmentioning
confidence: 99%
“…However, because of its high-affinity ligand binding ability, sFlt1 acts as a negative modulator by trapping VEGF-A, VEGF-B, and PlGF, preventing neovascularization promoted by these cytokines (25)(26)(27). It has been shown that sFlt1 inhibits tumor angiogenesis (28) and metastasis (29), binds lipid microdomains in kidney podocytes to control cell morphology and glomerular barrier function (30), regulates tip cell formation and branching morphogenesis in the zebra fish embryo (31), and plays a causal role in the pathogenesis of preeclampsia (32). In clinical settings, sFlt1 levels are of prognostic value in acute myocardial infarction (33).…”
mentioning
confidence: 99%